Valorisation of Polymetallic Hydroxide Sludge as Pollutant Trappers - Perrin, Loic; Laforest, Valerie; Bourgois, Jacques (Recent Patents on Chemical Engineering, 2009)
Metal finishing industries produce an important tonnage of metal hydroxide sludge (MHS) during the treatment of their liquid effluents charged with heavy metals. Generally, a small part of these sludge is valorized because of their important metal fickleness. Consequently, the majority of these metal hydroxide sludge is sent to landfill centers. We propose to valorize this sludge by using them as pollutant sorbent in order to retain the polluting species contained in the industrial aqueous effluents. The chosen pollutant for this preliminary study is Chromium (+VI). Starting from an experimental well defined protocol, various parameters have been studied (chemical nature of the sludge, solid/liquid ratio, concentration of the pollutant, particle size) in order to determine the experimental parameters which influence the sorption yield of these sludge and thus to validate the feasibility of an industrial application of this new way of valorisation. First results point out that the sorption yield is more than 95% independently from the experimental conditions. Moreover, experiments highlight that the sludge mass (and so sorbent sites) is THE only real parameter which influences the yield. In this article, a review of the patents on different aspects of the valorisation of polymetallic hydroxide sludge as pollutant trappers is presented.
Keywords: polymetallic hydroxide sludge